Process for the production of high-friction heavy-bag
Patent Information
- Application Number
- CN202611210107.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]重包袋作为一种关键的大宗货物包装工具,在化工、粮食、建材等诸多工业领域中得到广泛应用,用于承载粉末、颗粒或块状物料;然而,目前市场上常见的重包袋多数采用单一的聚乙烯、聚丙烯等高分子物质作为基质进行生产,故而在使用时普遍存在摩擦系数不足的缺陷,导致在堆垛操作时容易发生滑落现象,不仅可能造成物料损坏、污染环境,还可能引发人员伤亡和设备事故,从而显著增加了仓储与运输环节中的安全风险与管理成本,尤其在高层堆叠或长途物流时更加增加了安全风险
本发明制备的高摩擦重包袋具有良好的摩擦性能与综合力学特性,从而在进行物料堆放时增加相邻重包袋之间的摩擦力,从而降低装有物料的重包袋滑落情况的发生概率,降低了物料堆垛、物料运输、物料存储过程中安全风险,确保安全生产;
Smart Images

Figure CN123001292A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heavy-duty bags, specifically the production process of high-friction heavy-duty bags. Background Technology
[0002] Heavy-duty bags, as a crucial packaging tool for bulk goods, are widely used in many industrial sectors such as chemicals, food, and building materials to carry powders, granules, or lumpy materials. However, most heavy-duty bags on the market are currently produced using single polymer materials such as polyethylene and polypropylene as the matrix. As a result, they generally suffer from insufficient friction coefficients, which makes them prone to slippage during stacking operations. This can not only cause material damage and environmental pollution but also lead to personal injury and equipment accidents, thus significantly increasing safety risks and management costs in warehousing and transportation, especially during high-level stacking or long-distance logistics. Summary of the Invention
[0003] This invention provides a manufacturing process for high-friction heavy-duty bags to overcome the deficiencies in the prior art.
[0004] This invention is achieved through the following technical solution: The manufacturing process of high-friction heavy-duty bags includes the following steps: Step 1: Weigh out the high friction elastomer, polyurethane, polyethylene terephthalate, silica powder, dipentaerythritol, dioctadecyl thiodipropionate, and epoxy oleate according to the formula, mix them, and send them into a mixer for mixing and melting to obtain the outer melt. Step 2: Weigh out the polyolefin elastomer, polypropylene, flax staple fiber, mica powder, ethylene-methacrylic acid copolymer, calcium stearate, dilauryl thiodipropionate, and monostearate citrate according to the formula, mix them and send them into a mixer for mixing and melting to obtain the core layer melt. Step 3: Weigh out maleic anhydride-grafted polyethylene, polybutene, pentaerythritol tetrapalmitate, calcium laurate, polyethylene glycol distearate, rosin pentaerythritol ester, and 2,2'-methylenebis(4-methyl-6-tert-butylphenol) according to the formula, mix them and send them to a mixer for mixing and melting to obtain the inner layer melt. Step 4: The outer layer melt, core layer melt, and inner layer melt are fed into the corresponding feed channels of the co-extrusion compounding machine, so that the three layers of melt are fully fused at the die head and extruded into a composite film; then the composite film is cooled and shaped by cooling rollers. Step 5: Perform corona treatment on the outer layer of the shaped composite film; Step Six: After the corona treatment is completed, cut the bag according to the predetermined size, seal the bottom and sides of the bag using a heat-sealing process, and air-cool to room temperature to obtain a high-friction heavy-duty bag.
[0005] In the production process of high-friction heavy-duty bags as described above, the mass fraction of each substance in step one is as follows: 50-60 parts of high-friction elastomer, 40-50 parts of polyurethane, 15-25 parts of polyethylene terephthalate, 8-10 parts of silica powder, 4-6 parts of dipentaerythritol, 0.6-0.8 parts of dioctadecyl thiodipropionate, and 0.6-0.8 parts of epoxy oleate. The melting and mixing temperature in step one is 250-260℃, the melting and mixing stirring speed is 270-330 rad / min, and the melting and mixing treatment time is 40-50 min; The polyurethane has a number-average molecular weight of 100,000-140,000; The number-average molecular weight of the polyethylene terephthalate is 20,000-30,000; The silica powder has a mesh size of 800-1000 mesh.
[0006] The high-friction heavy-duty bag manufacturing process described above includes the following high-friction elastomer in parts by weight: 40-50 parts TPE elastomer, 35-40 parts SEBS elastomer, 15-20 parts polyketone resin, 6-8 parts naphthenic oil, 10-12 parts heavy calcium carbonate powder, 1.2-1.6 parts zinc stearate, 0.6-0.8 parts Fischer-Tropsch wax, 0.8-1.2 parts ethylene glycol dimethacrylate, and 0.2-0.4 parts di-tert-butyl phthalate peroxide; The number-average molecular weight of the TPE elastomer is 150,000-170,000; The number-average molecular weight of the SEBS elastomer is 200,000-300,000; The number-average molecular weight of the polyketone resin is 60,000-80,000; The density of the heavy calcium carbonate powder is 1200-1400 mesh.
[0007] The manufacturing process for high-friction heavy-duty bags as described above includes the following steps: Step 1: Weigh out the following components according to the specified ratio: TPE elastomer, SEBS elastomer, polyketone resin, naphthenic oil, heavy calcium carbonate powder, zinc stearate, Fischer-Tropsch wax, ethylene glycol dimethacrylate, and di-tert-butyl peroxide. Step 2: Add TPE elastomer, SEBS elastomer, and polyketone resin to a sealed reactor, heat to 190-200℃, and stir and melt at a speed of 150-200 rad / min for 50-60 minutes. Step 3: Add ethylene glycol dimethacrylate and di-tert-butyl peroxide to the sealed reaction vessel, raise the temperature to 210-220℃, and react for 70-90 min at a rotation speed of 200-250 rad / min. Step 4: Reduce the temperature of the sealed reactor to 180-190℃, then add naphthenic oil, heavy calcium carbonate powder, zinc stearate, and Fischer-Tropsch wax, and stir and melt at a speed of 250-300 rad / min for 20-30 min. Step 5: Transfer the molten material in the sealed reactor into a twin-screw extruder. The screw speed of the twin-screw extruder is controlled at 180-220 rad / min, and the temperature of the twin-screw extruder is controlled at 190-200℃. After the molten material is extruded by the extruder, it is pelletized by a pelletizer, and the resulting pellets are air-cooled to room temperature. Step 6: After the particles obtained in Step 5 are crushed, they are passed through a 200-mesh sieve to obtain a high-friction elastomer.
[0008] In the production process of high-friction heavy-duty bags as described above, the mass fraction of each substance in step two is as follows: 50-60 parts of polyolefin elastomer, 20-30 parts of polypropylene, 6-10 parts of flax staple fiber, 3-5 parts of mica powder, 6-8 parts of ethylene-methacrylic acid copolymer, 1-2 parts of calcium stearate, 0.6-0.8 parts of dilauryl thiodipropionate, and 1-2 parts of citrate monostearate. The melting and mixing temperature in step two is 160-170℃, the melting and mixing stirring speed is 250-300 rad / min, and the melting and mixing time is 30-40 min; The number-average molecular weight of the polyolefin elastomer is 150,000-190,000; The polypropylene has a number-average molecular weight of 80,000-120,000. The number-average molecular weight of the ethylene-methacrylic acid copolymer is 110,000-150,000; The flax short fibers have a mesh count of 600-800 mesh; The mica powder has a mesh size of 800-1000 mesh.
[0009] In the production process of high-friction heavy-duty bags as described above, the mass fraction of each substance in step three is as follows: maleic anhydride-grafted polyethylene 50-60 parts, polybutene 30-40 parts, pentaerythritol tetrapalmitate 1-2 parts, calcium laurate 2-4 parts, polyethylene glycol distearate 1-2 parts, rosin pentaerythritol ester 1-2 parts, and 2,2'-methylenebis(4-methyl-6-tert-butylphenol) 0.6-0.8 parts; The melting and mixing temperature in step three is 150-160℃, the melting and mixing stirring speed is 200-250 rad / min, and the melting and mixing time is 25-35 min; The grafting rate of the maleic anhydride-grafted polyethylene is 0.8-1.2%, and the number-average molecular weight is 80,000-120,000. The number-average molecular weight of the polybutene is 100,000-140,000.
[0010] In the production process of high-friction heavy-duty bags as described above, the temperature of the outer layer feed channel of the co-extrusion composite machine in step four is controlled at 250-260℃, the temperature of the core layer feed channel is controlled at 160-170℃, and the temperature of the inner layer feed channel is controlled at 150-160℃; the die head temperature is set at 220-240℃, the extrusion speed is 5-8m / min; the surface temperature of the cooling roller is controlled at 25-30℃, and the residence time of the composite film on the cooling roller is 10-15s.
[0011] In the production process of high-friction heavy-duty bags described above, the corona treatment voltage in step five is 15-20kV, the distance between the electrode and the outer layer of the composite film is set to 1.4-1.8mm, and the processing speed of the composite film is 3-5m / min; during the processing, the surface of the composite film must be kept flat and wrinkle-free.
[0012] In the production process of high-friction heavy-duty bags as described above, the temperature of the heat sealing process in step six is 170-180℃, the heat sealing pressure is 0.4-0.6MPa, and the heat sealing time is 2-3s.
[0013] The advantages of this invention are: The high-friction heavy-duty bags prepared by this invention have good friction performance and comprehensive mechanical properties, thereby increasing the friction between adjacent heavy-duty bags when stacking materials, thus reducing the probability of material-filled heavy-duty bags slipping off, reducing safety risks during material stacking, material transportation and material storage, and ensuring safe production; The outer layer of this invention uses a high-friction elastomer as the core functional component, combined with polyurethane and polyethylene terephthalate to form a composite matrix, thereby giving the outer layer both good mechanical properties and a high coefficient of friction. Silica powder can further increase the micro-roughness of the outer layer surface, improve the static friction coefficient, and effectively prevent slippage. Dipentaerythritol can enhance the crosslinking density of the composite matrix, further improving the wear resistance and structural stability of the outer layer. Dioctyl thiodipropionate and epoxy oleate can effectively inhibit the oxidative degradation of the material during long-term use, extend the service life of the outer layer, and improve the processing fluidity of the matrix, ensuring uniform dispersion of each component. The core layer of this invention is based on polyolefin elastomer and polypropylene, with flax short fibers and mica powder added as reinforcing fillers. This ensures the toughness of the core layer while improving the overall tear resistance. Ethylene-methacrylic acid copolymer can effectively improve the interfacial compatibility between the polyolefin elastomer and the polypropylene matrix, reduce phase separation, and enhance the internal bonding force of the material. Calcium stearate can reduce the frictional resistance between materials during processing, improve molding flowability, and increase production efficiency. Dilauryl thiodipropionate can capture free radicals, slow down the oxidative degradation rate of the core layer material under long-term use, and extend its service life. Citric acid monostearate helps to uniformly disperse flax short fibers and mica powder in the matrix, avoids filler agglomeration, and fully exerts its reinforcing effect. The inner layer of this invention uses maleic anhydride-grafted polyethylene and polybutene. The synergistic effect of the two provides good chemical resistance and sealing properties, effectively preventing leakage and moisture absorption of internal materials. Pentaerythritol tetrapalmitate enhances the flexibility and processing fluidity of the material. Calcium laurate improves thermal stability and anti-aging ability. Polyethylene glycol distearate helps improve the compatibility between the components. Rosin pentaerythritol ester improves the bonding strength and weather resistance of the material. 2,2'-methylenebis(4-methyl-6-tert-butylphenol) effectively inhibits the oxidative degradation of the material during long-term use, ensuring the stability and service life of the inner layer structure. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0015] Figure 1 This is a schematic diagram showing the results of friction coefficient testing between the high-friction heavy-duty bags prepared in Examples 1-3 of this invention and the heavy-duty bags prepared in the comparative example; Figure 2 This is a schematic diagram showing the tensile strength test results of the high-friction heavy-duty bags prepared in Examples 1-3 of the present invention and the heavy-duty bags prepared in the comparative example; Figure 3 This is a schematic diagram showing the results of breaking elongation testing of the high-friction heavy-duty bags prepared in Examples 1-3 of this invention and the heavy-duty bags prepared in the comparative example. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1
[0018] Step 1: Weigh out 50 parts of high-friction elastomer, 40 parts of polyurethane (number average molecular weight of 100,000), 15 parts of polyethylene terephthalate (number average molecular weight of 20,000), 8 parts of 800-mesh silica powder, 4 parts of dipentaerythritol, 0.6 parts of dioctadecyl thiodipropionate, and 0.6 parts of epoxy oleate according to the formula. Mix them and send them into a mixer for mixing and melting to obtain the outer melt. The melting and mixing temperature is 250℃, the melting and mixing stirring speed is 270 rad / min, and the melting and mixing time is 50 min. The preparation method of the high-friction elastomer includes the following steps: Step 1: Weigh out the following components according to the specified ratio: 40 parts of TPE elastomer (number average molecular weight 150,000), 35 parts of SEBS elastomer (number average molecular weight 200,000), 15 parts of polyketide resin (number average molecular weight 60,000), 6 parts of naphthenic oil, 10 parts of 1200-mesh heavy calcium carbonate powder, 1.2 parts of zinc stearate, 0.6 parts of Fischer-Tropsch wax, 0.8 parts of ethylene glycol dimethacrylate, and 0.2 parts of di-tert-butyl peroxide. Step 2: Add TPE elastomer, SEBS elastomer, and polyketone resin to a sealed reactor, heat to 190℃, and stir and melt at a speed of 150 rad / min for 60 min. Step 3: Add ethylene glycol dimethacrylate and di-tert-butyl peroxide to a sealed reaction vessel, raise the temperature to 210°C, and react for 90 min at a rotation speed of 200 rad / min. Step 4: The temperature of the sealed reactor is reduced to 180℃, and then naphthenic oil, heavy calcium carbonate powder, zinc stearate and Fischer-Tropsch wax are added. The mixture is stirred and melted at a speed of 250 rad / min for 30 min. Step 5: Transfer the molten material in the sealed reactor into a twin-screw extruder. The screw speed of the twin-screw extruder is controlled at 180 rad / min, and the temperature of the twin-screw extruder is controlled at 190℃. After the molten material is extruded by the extruder, it is pelletized by a pelletizer, and the resulting pellets are air-cooled to room temperature. Step 6: The high-friction elastomer obtained in Step 5 is obtained by crushing the granules and passing them through a 200-mesh sieve; Step 2: Weigh out 50 parts of polyolefin elastomer (number average molecular weight 150,000), 20 parts of polypropylene (number average molecular weight 80,000), 6 parts of 600-mesh flax staple fiber, 3 parts of 800-mesh mica powder, 6 parts of ethylene-methacrylic acid copolymer (number average molecular weight 110,000), 1 part of calcium stearate, 0.6 parts of dilauryl thiodipropionate, and 1 part of citrate monostearate according to the specified ratio. Mix them and send them to a mixer for melting to obtain the core layer melt. The melting temperature is 160℃, the melting stirring speed is 250 rad / min, and the melting time is 40 min. Step 3: Weigh out 50 parts of maleic anhydride-grafted polyethylene (grafting rate 0.8%, number average molecular weight 80,000), 30 parts of polybutene (number average molecular weight 100,000), 1 part of pentaerythritol tetrapalmitate, 2 parts of calcium laurate, 1 part of polyethylene glycol distearate, 1 part of rosin pentaerythritol ester, and 0.6 parts of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) according to the formula. Mix them and send them to a mixer for mixing and melting to obtain the inner layer melt. The melting and mixing temperature is 150℃, the melting and mixing stirring speed is 200 rad / min, and the melting and mixing treatment time is 35 min. Step 4: The outer layer melt, core layer melt, and inner layer melt are fed into the corresponding feed channels of the co-extrusion compounding machine. The temperature of the outer layer feed channel is controlled at 250℃, the core layer feed channel at 160℃, and the inner layer feed channel at 150℃, so that the three layers of melt are fully fused at the die head and extruded into a composite film. The die head temperature is set to 220℃, and the extrusion speed is 5m / min. Subsequently, the composite film is cooled and shaped by cooling rollers. The surface temperature of the cooling rollers is controlled at 25℃, and the residence time of the composite film on the cooling rollers is 15s, resulting in a composite film with a thickness of 0.15±0.02mm. Step 5: Perform corona treatment on the outer layer of the shaped composite membrane. The corona treatment voltage is 15kV, the distance between the electrode and the outer layer of the composite membrane is set to 1.4mm, and the processing speed of the composite membrane is 3m / min. During the processing, the surface of the composite membrane must be kept flat and wrinkle-free. Step Six: After the corona treatment is completed, cut the bag to 600mm×1000mm. Use a heat-sealing process to seal the bottom and sides of the bag. The heat-sealing temperature is 170℃, the heat-sealing pressure is 0.4MPa, and the heat-sealing time is 3s. After air cooling to room temperature, a high-friction heavy-duty bag is obtained.
[0019] Example 2
[0020] Step 1: Weigh out 60 parts of high-friction elastomer, 50 parts of polyurethane (number average molecular weight 140,000), 25 parts of polyethylene terephthalate (number average molecular weight 30,000), 10 parts of 1000-mesh silica powder, 6 parts of dipentaerythritol, 0.8 parts of dioctadecyl thiodipropionate, and 0.8 parts of epoxy oleate according to the specified ratio. Mix them and send them into a mixer for melting to obtain the outer melt. The melting temperature is 260℃, the stirring speed is 330 rad / min, and the melting time is 40 min. The preparation method of the high-friction elastomer includes the following steps: Step 1: Weigh out the following components according to the specified ratio: 50 parts TPE elastomer (number average molecular weight 170,000), 40 parts SEBS elastomer (number average molecular weight 300,000), 20 parts polyketide resin (number average molecular weight 80,000), 8 parts naphthenic oil, 12 parts 1400-mesh heavy calcium carbonate powder, 1.6 parts zinc stearate, 0.8 parts Fischer-Tropsch wax, 1.2 parts ethylene glycol dimethacrylate, and 0.4 parts di-tert-butyl peroxide. Step 2: Add TPE elastomer, SEBS elastomer, and polyketone resin to a sealed reactor, heat to 200℃, and stir and melt at a speed of 200 rad / min for 50 min. Step 3: Add ethylene glycol dimethacrylate and di-tert-butyl peroxide to a sealed reaction vessel, raise the temperature to 220°C, and react for 70 min at a rotation speed of 250 rad / min. Step 4: The temperature of the sealed reactor is reduced to 190℃, and then naphthenic oil, heavy calcium carbonate powder, zinc stearate and Fischer-Tropsch wax are added. The mixture is stirred and melted at a speed of 300 rad / min for 20 min. Step 5: Transfer the molten material in the sealed reactor into a twin-screw extruder. The screw speed of the twin-screw extruder is controlled at 220 rad / min, and the temperature of the twin-screw extruder is controlled at 200℃. After the molten material is extruded by the extruder, it is pelletized by a pelletizer, and the resulting pellets are air-cooled to room temperature. Step 6: The high-friction elastomer obtained in Step 5 is obtained by crushing the granules and passing them through a 200-mesh sieve; Step 2: Weigh out 60 parts of polyolefin elastomer (number average molecular weight 190,000), 30 parts of polypropylene (number average molecular weight 120,000), 10 parts of 800-mesh flax staple fiber, 5 parts of 1000-mesh mica powder, 8 parts of ethylene-methacrylic acid copolymer (number average molecular weight 150,000), 2 parts of calcium stearate, 0.8 parts of dilauryl thiodipropionate, and 2 parts of citrate monostearate according to the specified ratio. Mix them and send them to a mixer for melting to obtain the core layer melt. The melting temperature is 170℃, the melting stirring speed is 300 rad / min, and the melting time is 30 min. Step 3: Weigh out 60 parts of maleic anhydride-grafted polyethylene (grafting rate 1.2%, number average molecular weight 120,000), 40 parts of polybutene (number average molecular weight 140,000), 2 parts of pentaerythritol tetrapalmitate, 4 parts of calcium laurate, 2 parts of polyethylene glycol distearate, 2 parts of rosin pentaerythritol ester, and 0.8 parts of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) according to the formula. Mix them and send them to a mixer for mixing and melting to obtain the inner layer melt. The melting and mixing temperature is 160℃, the melting and mixing stirring speed is 250 rad / min, and the melting and mixing treatment time is 25 min. Step 4: The outer layer melt, core layer melt, and inner layer melt are fed into the corresponding feed channels of the co-extrusion compounding machine. The temperature of the outer layer feed channel is controlled at 260℃, the core layer feed channel at 170℃, and the inner layer feed channel at 160℃, so that the three layers of melt are fully fused at the die head and extruded into a composite film. The die head temperature is set to 240℃, and the extrusion speed is 8m / min. Subsequently, the composite film is cooled and shaped by cooling rollers. The surface temperature of the cooling rollers is controlled at 30℃, and the residence time of the composite film on the cooling rollers is 10s, resulting in a composite film with a thickness of 0.15±0.02mm. Step 5: Perform corona treatment on the outer layer of the shaped composite membrane. The corona treatment voltage is 20kV, the distance between the electrode and the outer layer of the composite membrane is set to 1.8mm, and the processing speed of the composite membrane is 5m / min. During the processing, the surface of the composite membrane must be kept flat and wrinkle-free. Step Six: After the corona treatment is completed, cut the bag to 600mm×1000mm. Use a heat-sealing process to seal the bottom and sides of the bag. The heat-sealing temperature is 180℃, the heat-sealing pressure is 0.6MPa, and the heat-sealing time is 2s. After air cooling to room temperature, a high-friction heavy-duty bag is obtained.
[0021] Example 3
[0022] Step 1: Weigh out 55 parts of high-friction elastomer, 45 parts of polyurethane (number average molecular weight 120,000), 20 parts of polyethylene terephthalate (number average molecular weight 25,000), 9 parts of 900-mesh silica powder, 5 parts of dipentaerythritol, 0.7 parts of dioctadecyl thiodipropionate, and 0.7 parts of epoxy oleate according to the specified ratio. Mix them and send them to a mixer for melting to obtain the outer melt. The melting temperature is 255℃, the stirring speed is 300 rad / min, and the melting time is 45 min. The preparation method of the high-friction elastomer includes the following steps: Step 1: Weigh out the following components according to the specified ratio: 45 parts TPE elastomer (number average molecular weight 160,000), 37.5 parts SEBS elastomer (number average molecular weight 250,000), 17.5 parts polyketide resin (number average molecular weight 70,000), 7 parts naphthenic oil, 11 parts 1300-mesh heavy calcium carbonate powder, 1.4 parts zinc stearate, 0.7 parts Fischer-Tropsch wax, 1.0 part ethylene glycol dimethacrylate, and 0.3 parts di-tert-butyl peroxide. Step 2: Add TPE elastomer, SEBS elastomer, and polyketone resin to a sealed reactor, heat to 195℃, and stir and melt at a speed of 175 rad / min for 55 min. Step 3: Add ethylene glycol dimethacrylate and di-tert-butyl peroxide to a sealed reaction vessel, raise the temperature to 215°C, and react for 80 min at a rotation speed of 225 rad / min. Step 4: The temperature of the sealed reactor is reduced to 185℃, and then naphthenic oil, heavy calcium carbonate powder, zinc stearate and Fischer-Tropsch wax are added. The mixture is stirred and melted at a speed of 275 rad / min for 25 min. Step 5: Transfer the molten material in the sealed reactor into a twin-screw extruder. The screw speed of the twin-screw extruder is controlled at 200 rad / min, and the temperature of the twin-screw extruder is controlled at 195℃. After the molten material is extruded by the extruder, it is pelletized by a pelletizer, and the resulting pellets are air-cooled to room temperature. Step 6: The high-friction elastomer obtained in Step 5 is obtained by crushing the granules and passing them through a 200-mesh sieve; Step 2: Weigh out 55 parts of polyolefin elastomer (number average molecular weight 170,000), 25 parts of polypropylene (number average molecular weight 100,000), 8 parts of 700-mesh flax staple fiber, 4 parts of 900-mesh mica powder, 7 parts of ethylene-methacrylic acid copolymer (number average molecular weight 130,000), 1.5 parts of calcium stearate, 0.7 parts of dilauryl thiodipropionate, and 1.5 parts of citrate monostearate according to the specified ratio. Mix them and send them to a mixer for melting to obtain the core layer melt. The melting temperature is 165℃, the melting stirring speed is 275 rad / min, and the melting time is 35 min. Step 3: Weigh out 55 parts of maleic anhydride-grafted polyethylene (grafting rate 1.0%, number average molecular weight 100,000), 35 parts of polybutene (number average molecular weight 120,000), 1.5 parts of pentaerythritol tetrapalmitate, 3 parts of calcium laurate, 1.5 parts of polyethylene glycol distearate, 1.5 parts of rosin pentaerythritol ester, and 0.7 parts of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) according to the formula. Mix them and send them to a mixer for mixing and melting to obtain the inner layer melt. The melting and mixing temperature is 155℃, the melting and mixing stirring speed is 225 rad / min, and the melting and mixing time is 30 min. Step 4: The outer layer melt, core layer melt, and inner layer melt are fed into the corresponding feed channels of the co-extrusion compounding machine. The temperature of the outer layer feed channel is controlled at 255℃, the core layer feed channel at 165℃, and the inner layer feed channel at 155℃, so that the three layers of melt are fully fused at the die head and extruded into a composite film. The die head temperature is set to 230℃, and the extrusion speed is 6.5m / min. Subsequently, the composite film is cooled and shaped by cooling rollers. The surface temperature of the cooling rollers is controlled at 27.5℃, and the residence time of the composite film on the cooling rollers is 12.5s, resulting in a composite film with a thickness of 0.15±0.02mm. Step 5: Perform corona treatment on the outer layer of the shaped composite membrane. The corona treatment voltage is 17.5kV, the distance between the electrode and the outer layer of the composite membrane is set to 1.6mm, and the processing speed of the composite membrane is 4m / min. During the processing, the surface of the composite membrane must be kept flat and wrinkle-free. Step Six: After the corona treatment is completed, cut the bag to 600mm×1000mm. Use a heat-sealing process to seal the bottom and sides of the bag. The heat-sealing temperature is 175℃, the heat-sealing pressure is 0.5MPa, and the heat-sealing time is 2.5s. After air cooling to room temperature, a high-friction heavy-duty bag is obtained.
[0023] Comparative Example 1 Step 1: Weigh out 100 parts of polypropylene (number average molecular weight 100,000), 20 parts of polyethylene (number average molecular weight 50,000), 9 parts of 900-mesh silica powder, 5 parts of dipentaerythritol, 0.7 parts of dioctadecyl thiodipropionate, and 0.7 parts of epoxy oleate according to the formula. Mix them and send them to a mixer for mixing and melting to obtain the outer melt. The melting and mixing temperature is 255℃, the melting and mixing stirring speed is 300 rad / min, and the melting and mixing time is 45 min. Step 2: Weigh out 55 parts of polyethylene (number average molecular weight of 50,000), 25 parts of polypropylene (number average molecular weight of 100,000), 8 parts of 700-mesh flax staple fiber, 4 parts of 900-mesh mica powder, 7 parts of ethylene-methacrylic acid copolymer (number average molecular weight of 130,000), 1.5 parts of calcium stearate, 0.7 parts of dilauryl thiodipropionate, and 1.5 parts of citrate monostearate according to the specified ratio. Mix them and send them to a mixer for melting to obtain the core layer melt. The melting temperature is 165℃, the melting stirring speed is 275 rad / min, and the melting time is 35 min. Step 3: Weigh out 55 parts of polyethylene (number average molecular weight of 50,000), 35 parts of polybutene (number average molecular weight of 120,000), 1.5 parts of pentaerythritol tetrapalmitate, 3 parts of calcium laurate, 1.5 parts of polyethylene glycol distearate, 1.5 parts of rosin pentaerythritol ester, and 0.7 parts of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) according to the formula. Mix them and send them to a mixer for mixing and melting to obtain the inner layer melt. The melting and mixing temperature is 155℃, the melting and mixing stirring speed is 225 rad / min, and the melting and mixing time is 30 min. Step 4: The outer layer melt, core layer melt, and inner layer melt are fed into the corresponding feed channels of the co-extrusion compounding machine. The temperature of the outer layer feed channel is controlled at 255℃, the core layer feed channel at 165℃, and the inner layer feed channel at 155℃, so that the three layers of melt are fully fused at the die head and extruded into a composite film. The die head temperature is set to 230℃, and the extrusion speed is 6.5m / min. Subsequently, the composite film is cooled and shaped by cooling rollers. The surface temperature of the cooling rollers is controlled at 27.5℃, and the residence time of the composite film on the cooling rollers is 12.5s, resulting in a composite film with a thickness of 0.15±0.02mm. Step 5: After the corona treatment is completed, cut the bag to 600mm×1000mm. Use a heat-sealing process to seal the bottom and sides of the bag. The heat-sealing temperature is 175℃, the heat-sealing pressure is 0.5MPa, and the heat-sealing time is 2.5s. After air cooling to room temperature, the repackaged bag is obtained.
[0024] The high-friction heavy-duty bags prepared in Examples 1-3 and the comparative example were subjected to tests on the outer layer friction coefficient (the test method refers to GB / T10006-2021 "Determination of Friction Coefficient of Plastic Films and Sheets"), tensile strength (the test method refers to GB / T1040.3-2023 "Determination of Tensile Properties of Plastics"), and elongation at break (the test method refers to GB / T1040.3-2023 "Determination of Tensile Properties of Plastics"). Five samples were taken for each test, and the average value was recorded. The test results are as follows: Figures 1-3 As shown.
[0025] Depend on Figures 1-3 Data shows that the high-friction heavy-duty bags prepared in Examples 1-3 of this invention are superior to the comparative heavy-duty bags in terms of three core performance indicators: coefficient of friction, tensile strength, and elongation at break. The coefficient of friction of the high-friction heavy-duty bags prepared in Examples 1-3 of this invention is higher than 0.7, which is much higher than the 0.48 of the comparative example. The tensile strength of the high-friction heavy-duty bags prepared in Examples 1-3 of this invention is higher than 49 MPa, which is much higher than the 29.3 MPa of the comparative example. The elongation at break of the high-friction heavy-duty bags prepared in Examples 1-3 of this invention is higher than 360%, which is also better than the 287% of the comparative example. Therefore, the high-friction heavy-duty bags prepared in this invention have good friction performance and comprehensive mechanical properties, thereby improving the stability of the heavy-duty bags during use and improving the safety of material stacking, transportation, and storage operations.
[0026] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. The manufacturing process of high-friction heavy-duty bags, characterized by: Includes the following steps: Step 1: Weigh out the high friction elastomer, polyurethane, polyethylene terephthalate, silica powder, dipentaerythritol, dioctadecyl thiodipropionate, and epoxy oleate according to the formula, mix them, and send them into a mixer for mixing and melting to obtain the outer melt. Step 2: Weigh out the polyolefin elastomer, polypropylene, flax staple fiber, mica powder, ethylene-methacrylic acid copolymer, calcium stearate, dilauryl thiodipropionate, and monostearate citrate according to the formula, mix them and send them into a mixer for mixing and melting to obtain the core layer melt. Step 3: Weigh out maleic anhydride-grafted polyethylene, polybutene, pentaerythritol tetrapalmitate, calcium laurate, polyethylene glycol distearate, rosin pentaerythritol ester, and 2,2'-methylenebis(4-methyl-6-tert-butylphenol) according to the formula, mix them and send them to a mixer for mixing and melting to obtain the inner layer melt. Step 4: The outer layer melt, core layer melt, and inner layer melt are fed into the corresponding feed channels of the co-extrusion compounding machine, so that the three layers of melt are fully fused at the die head and extruded into a composite film; then the composite film is cooled and shaped by cooling rollers. Step 5: Perform corona treatment on the outer layer of the shaped composite film; Step Six: After the corona treatment is completed, cut the bag according to the predetermined size, seal the bottom and sides of the bag using a heat-sealing process, and air-cool to room temperature to obtain a high-friction heavy-duty bag.
2. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: The mass fractions of each substance in step one are as follows: 50-60 parts of high-friction elastomer, 40-50 parts of polyurethane, 15-25 parts of polyethylene terephthalate, 8-10 parts of silica powder, 4-6 parts of dipentaerythritol, 0.6-0.8 parts of dioctadecyl thiodipropionate, and 0.6-0.8 parts of epoxy oleate. The melting and mixing temperature in step one is 250-260℃, the melting and mixing stirring speed is 270-330 rad / min, and the melting and mixing treatment time is 40-50 min; The polyurethane has a number-average molecular weight of 100,000-140,000; The number-average molecular weight of the polyethylene terephthalate is 20,000-30,000; The silica powder has a mesh size of 800-1000 mesh.
3. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: The high-friction elastomer comprises the following components in parts by weight: 40-50 parts TPE elastomer, 35-40 parts SEBS elastomer, 15-20 parts polyketone resin, 6-8 parts naphthenic oil, 10-12 parts heavy calcium carbonate powder, 1.2-1.6 parts zinc stearate, 0.6-0.8 parts Fischer-Tropsch wax, 0.8-1.2 parts ethylene glycol dimethacrylate, and 0.2-0.4 parts di-tert-butyl peroxide. The number-average molecular weight of the TPE elastomer is 150,000-170,000; The number-average molecular weight of the SEBS elastomer is 200,000-300,000; The number-average molecular weight of the polyketone resin is 60,000-80,000; The density of the heavy calcium carbonate powder is 1200-1400 mesh.
4. The production process of the high-friction heavy-duty bag according to claim 3, characterized in that: Its preparation method includes the following steps: Step 1: Weigh out the following components according to the specified ratio: TPE elastomer, SEBS elastomer, polyketone resin, naphthenic oil, heavy calcium carbonate powder, zinc stearate, Fischer-Tropsch wax, ethylene glycol dimethacrylate, and di-tert-butyl peroxide. Step 2: Add TPE elastomer, SEBS elastomer, and polyketone resin to a sealed reactor, heat to 190-200℃, and stir and melt at a speed of 150-200 rad / min for 50-60 minutes. Step 3: Add ethylene glycol dimethacrylate and di-tert-butyl peroxide to the sealed reaction vessel, raise the temperature to 210-220℃, and react for 70-90 min at a rotation speed of 200-250 rad / min. Step 4: Reduce the temperature of the sealed reactor to 180-190℃, then add naphthenic oil, heavy calcium carbonate powder, zinc stearate, and Fischer-Tropsch wax, and stir and melt at a speed of 250-300 rad / min for 20-30 min. Step 5: Transfer the molten material in the sealed reactor into a twin-screw extruder. The screw speed of the twin-screw extruder is controlled at 180-220 rad / min, and the temperature of the twin-screw extruder is controlled at 190-200℃. After the molten material is extruded by the extruder, it is pelletized by a pelletizer, and the resulting pellets are air-cooled to room temperature. Step 6: After the particles obtained in Step 5 are crushed, they are passed through a 200-mesh sieve to obtain a high-friction elastomer.
5. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: The mass fractions of each substance in step two are as follows: 50-60 parts of polyolefin elastomer, 20-30 parts of polypropylene, 6-10 parts of flax short fiber, 3-5 parts of mica powder, 6-8 parts of ethylene-methacrylic acid copolymer, 1-2 parts of calcium stearate, 0.6-0.8 parts of dilauryl thiodipropionate, and 1-2 parts of citrate monostearate. The melting and mixing temperature in step two is 160-170℃, the melting and mixing stirring speed is 250-300 rad / min, and the melting and mixing time is 30-40 min; The number-average molecular weight of the polyolefin elastomer is 150,000-190,000; The polypropylene has a number-average molecular weight of 80,000-120,000. The number-average molecular weight of the ethylene-methacrylic acid copolymer is 110,000-150,000; The flax short fibers have a mesh count of 600-800 mesh; The mica powder has a mesh size of 800-1000 mesh.
6. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: The mass fractions of each substance in step three are as follows: maleic anhydride-grafted polyethylene 50-60 parts, polybutene 30-40 parts, pentaerythritol tetrapalmitate 1-2 parts, calcium laurate 2-4 parts, polyethylene glycol distearate 1-2 parts, rosin pentaerythritol ester 1-2 parts, and 2,2'-methylenebis(4-methyl-6-tert-butylphenol) 0.6-0.8 parts; The melting and mixing temperature in step three is 150-160℃, the melting and mixing stirring speed is 200-250 rad / min, and the melting and mixing time is 25-35 min; The grafting rate of the maleic anhydride-grafted polyethylene is 0.8-1.2%, and the number-average molecular weight is 80,000-120,000. The number-average molecular weight of the polybutene is 100,000-140,000.
7. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: In step four, the temperature of the outer layer feed channel of the co-extrusion composite machine is controlled at 250-260℃, the temperature of the core layer feed channel is controlled at 160-170℃, and the temperature of the inner layer feed channel is controlled at 150-160℃; the die head temperature is set at 220-240℃, the extrusion speed is 5-8m / min; the surface temperature of the cooling roller is controlled at 25-30℃, and the residence time of the composite film on the cooling roller is 10-15s.
8. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: In step five, the corona treatment voltage is 15-20kV, the distance between the electrode and the outer layer of the composite film is set to 1.4-1.8mm, and the processing speed of the composite film is 3-5m / min; during the processing, the surface of the composite film must be kept flat and wrinkle-free.
9. The production process of the high-friction heavy-duty bag according to claim 1, characterized in that: In step six, the heat sealing process involves a temperature of 170-180℃, a heat sealing pressure of 0.4-0.6MPa, and a heat sealing time of 2-3 seconds.
